Land-use and food security in energy transition: Role of food supply - Zhuang, Daoyong; Abbas, Jaffar; Al-Sulaiti, Khalid; Fahlevi, Mochammad; Aljuaid, Mohammed; Saniuk, Sebastian (Frontiers in Sustainable Food Systems, 2022)
Food security in a just energy transition is a growing debate about designing sustainable food secure networks worldwide. Energy transition, land-use change, and food security are crucial factors for food security and provision. The increased demand for food products and customer preferences regarding food safety provide various issues for the current agriculture food supply chain (AFSC). Along with rising sustainability concerns, strict government regulation, food security, and traceability concerns compel managers, business houses, and practitioners working in AFSC to adopt new tools, techniques, and methodologies to model current food supply chain problems. Thus, in turn, design the food logistics network for food security. Hence, this study investigates the core determinants of food security and supply in Egypt, Morocco, Tunisia, and Lebanon from 2010 to 2019. Moreover, to estimate the study's objectives, we employ the fully modified ordinary least square (FMOLS) and dynamic ordinary least squares estimators (DOLS) to draw the study findings. However, the estimated results show a negative association of land use with food security and supply. Likewise, energy transition, gross domestic product, and agricultural value contribute to the food security supply. In contrast, urbanization's negative but insignificant contribution to the food supply in selected economies exists. Besides, another core objective of the study is to investigate the moderate role of the energy transition on the gross domestic product, agriculture sector, and land use and find the significant contribution to the food supply. However, the current study also tries forecasting for the next ten years and employs the impulse response function (IRF) and variance decomposition analysis (VDA). Also, this study uses the pairwise panel causality test and finds exciting outcomes. On behalf of outcomes, the current study proposes imperative policies to investigate the desired level of food supply.